KAJIAN KARAKTERISTIK BRIKET DARI PENCAMPURAN JERAMI DAN SEKAM PADI DARI LIMBAH PASCA PANEN DI LAHAN GAMBUT - Fonny Rianawati; Zainal Abidin; Muhammad Naparin (Lambung Mangkurat University-Indonesia, 2021)
This study aims to study the characteristics of briquettes from rice straw and rice husks in the form of moisture content, density, ash content, flight substance content, and heating value with different mixing variations in an effort to overcome the occurrence of deep forest / land fires to control forest or land fires in wetland areas by innovating and utilizing technology of straw and rice husks from post-harvest waste. The test results showed, the characteristic values are not much different for each mixing variation and are still below the Indonesian National Standard (SNI) No. 1-6235-2000, namely The heating value ranges from 2729.33 - 3492.14 cal/g (SNI ≥ 5000 cal/g), bonded carbon content ranges from 2.3524 -12.5870% (SNI ≥ 77%), ash content ranges from 27.3367 -29.8367% (SNI ≤ 8%) and the moisture content ranges from 18.2130 -28.8903% (SNI ≤ 8%). This is presumably due to the large content of the adhesive used, the pressing and drying processes that cause high water content, because high water content will cause a low calorific value. Low heating value will cause a large amount of ash content which causes a low value of bound carbon. However, overall charcoal briquettes from rice husks and rice straw can be applied to the community as a technological innovation that can be used in the use of post-harvest waste in an effort to control forest and land fires with land processing without burning.